Intra-articular injection with triamcinolone hexacetonide in patients with rheumatoid arthritis: prospective assessment of goniometry and joint inflammation parameters - Rita Nely Vilar Furtado; Flávia Soares Machado; Karine Rodrigues da Luz; Marla Francisca dos Santos; Monique Sayuri Konai; Roberta Vilela Lopes; Jamil Natour (Revista Brasileira de Reumatologia)
Abstract Objectives: To evaluate local joint variables after intra-articular injection with triamcinolone hexacetonide in rheumatoid arthritis patients. Methods: We blindly and prospectively (baseline, 1, 4, 12 and 24 weeks) evaluated metacarpophalangeal, wrist, elbow, shoulder, knee and ankle joints after triamcinolone hexacetonide intra-articular injection by the following outcome measures: visual analogue scale 0–10 cm (VAS) for rest pain (VASR); VAS for movement pain (VASM); VAS for joint swelling (VASSw); flexion (FlexG) and extension (ExtG). Results: 289 patients (635 joints) were studied. VASSw (p < 0.001) and VASR (0.001 < p < 0.016) improved from T0 to T4, T12 and T24 for all joints. VASM improved from T0 to T4 (p < 0.021) for all joints; T0 to T12 (p < 0.023) for MCF and knee; T0 to T24 (p < 0.019) only for MCF and knee. FlexG improved from T0 to T4 (p < 0.001) for all joints; T0 to T12 (p < 0.001) and T0 to T24 (p < 0.02) only for MCF and knee. ExtG improved from T0 to T4 (p < 0.001) for all joints except for elbow; T0 to T12 (p = 0.003) for wrist, metacarpophalangeal and knee; and T0 to T24 (p = 0.014) for MCF and knee. Conclusion: VASSw responded better at short and medium term after IAI with triamcinolone hexacetonide in our sample of RA patients.